Combination of rhomboid flap and double Z-plasty technique for reconstruction of palmar and dorsal web space burn contractures. Issue 2 (March 2015) - Sari, Elif; Tellioglu, Ali Teoman; Altuntas, Nurgul; Seven, Ergin; Ozakpinar, Hulda Rifat
Graphical abstract